Validitas dan Praktikalitas Modul Larutan Penyangga Berbasis Guided Discovery dengan Mengunakan Tiga Level Representasi Kimia untuk Kelas XI SMA - Nadya Dewara; Minda Azhar (Edukimia, 2019)
The 2013 curriculum requires teachers to use a scientific approach in teaching-learning process. The scientific approach is in accordance with the steps of various learning models, one of which is guided discovery. The study aimed at developing guided discovery modules on material buffer solutions for class XI SMA or MA and determining the validity and practicality of the developed modules. The research type was Research and Development. The development model was 4-D models that consists of four steps: define, design, develop, and disseminate. The research was limited to. The instrument of the research was questionnaire a form that consist of validity and practicality sheets. The module was validated by 5 validators and module practicality was examined by 2 chemistry teachers and 34 students of grade XI MIA 1 at SMAN 12 of Padang. Validity and practicality data were analysed by using the kappa Cohen formula. The moment kappa average of 5 validators was 0.90 with highest validity category. The moment kappa average of teachers and students were 0.8 and 0.86 spelling with the high category. The result of the research showed that the module of buffer solutions based on guided discovery with multiple representations was valid and practice to be used on the learning of chemistry.